(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was aimed at elucidating the association between Para influenza virus 3 (PIV3) and respiratory infections in domestic ruminants in different areas of Sudan. Materials and methods: During 2010-2013, five hundred sixty five lung samples with signs of pneumonia were collected from cattle (n=226), sheep (n=316) and goats (n=23) from slaughter houses in different areas in Sudan. The existence of PIV3 antigen was screened in the collected samples using ELISA and Fluorescent antibody technique. PIV3 genome was detected by PCR, and sequence analysis was conducted. Results: Positive results were found in 29 (12.8%) cattle, 31 (9.8%) sheep and 11 (47.8%) goat samples. All the studied areas showed positive results. Highest prevalence (66.7%) was detected in the sheep and goats in Khartoum, followed by in goats in Nyala (33.3%) at western Sudan. Sequence analyses of PIV3 of different regions of Sudan indicated that these were similar in sequence and length. The BLAST analysis indicated that the test sequences were closely related to the available annotated sequences at the GenBank. All these sequences matched with Bovine parainfluenza virus 3 except two those were matching with Swine parainfluenza virus 3. Conclusion: The results prove the existence of PIV3 infection in cattle, sheep and goats in the studied areas in Sudan and suggest its possible role in the respiratory infections. Genetic analysis indicate that the virus is mostly similar with bovine PIV3. http://doi.org/10.5455/javar.2016.c160